In Vitro Evaluation of Propolis Effects on Bacteroides fragilis Toxin-mediated Inflammatory Pathways - Soonjae HWANG; Yeram LEE; Ki-Jong RHEE (Korean Journal of Clinical Laboratory Science, 2025)
Colorectal cancer (CRC) remains a significant global health concern because of its increasing incidence and mortality rates. Chronic intestinal inflammation is a critical driver in the pathogenesis of CRC, particularly in individuals with inflammatory bowel disease (IBD), who face a heightened risk. The gut microbiota, including specific bacteria, such as enterotoxigenic Bacteroides fragilis (ETBF) and its secreted B. fragilis toxin (BFT), plays a crucial role in modulating these inflammatory processes. BFT disrupts the intestinal epithelial barrier by inducing E-cadherin cleavage, activating the pro-inflammatory signaling pathways, including NF-κB, and leading to the production of cytokines such as CXCL1. The current therapeutic options for ETBF infections, relying primarily on antibiotics, can have limitations, such as inducing dysbiosis, highlighting the need for alternative strategies. Propolis, a natural substance with reported antibacterial and anti-inflammatory properties, presents a promising alternative. This in vitro study examined the potential of propolis to counteract the BFT-induced disruption of E-cadherin and the associated inflammatory signaling in colonic epithelial cells. The findings showed that the propolis treatment effectively reduced the BFT-induced NF-κB activity and the expression of pro-inflammatory cytokines. These in vitro results suggest that propolis may be a therapeutic agent to mitigate ETBF-driven inflammation and help preserve the intestinal barrier.